2010
DOI: 10.3109/17482968.2010.536839
|View full text |Cite
|
Sign up to set email alerts
|

Depression in amyotrophic lateral sclerosis

Abstract: Depression is an under-recognized comorbidity associated with amyotrophic lateral sclerosis (ALS). The goals of this study were to prospectively estimate the prevalence of depression and other ALS related symptoms and to study the impact of depression on enrollment in research studies. One hundred and twenty-seven people with ALS completed the ALS Depression Inventory (ADI-12) and answered questions about ALS related symptoms and research study enrollment preferences. Demographics, ALS symptoms, medications, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 17 publications
(17 reference statements)
10
71
0
3
Order By: Relevance
“…23,24 Patients with ALS may be prescribed with antidepressants for reasons other than depression, such as excessive salivation where the anticholinergic side effect of antidepressants is desirable and emotional outbursts where the patients suddenly and without control cry or laugh. These possibilities likely explain the more pronounced risk increase for antidepressant use after ALS diagnosis, compared to depression diagnosis, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Patients with ALS may be prescribed with antidepressants for reasons other than depression, such as excessive salivation where the anticholinergic side effect of antidepressants is desirable and emotional outbursts where the patients suddenly and without control cry or laugh. These possibilities likely explain the more pronounced risk increase for antidepressant use after ALS diagnosis, compared to depression diagnosis, as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reductionism of Combe's distinction clearly emerges from the clinical observation given that a wide range of nervous system's illnesses with different etiology shows both neurological and psychiatric symptoms. Emotional and behavioral disturbances with a polymorphic symptomatology are often connected to neurological disorders such as Multiple Sclerosis (MS) [1][2][3] , Parkinson' s Disease (PD) [4] , stroke [5] , dementia [6] , traumatic brain injury [7] , epilepsy [8,9] , Amyotrophic Lateral Sclerosis (ALS) and others Motor Neuron Diseases (MND) [10,11] , pain syndromes (like headaches) and can be observed even with or without "organic" neurological diseases, thus miming in some cases an idiopathic psychiatric disorder.…”
Section: Neurology and Psychiatrymentioning
confidence: 99%
“…Systematic reviews concluded that major depression is uncommon, affecting between 6 and 12% of patients [12,13]. Recent studies report estimates of 6% for major and 29% for mild depression [14], of 22% for major and minor depression altogether [15]. In 13.5% of patients depression followed ALS diagnosis [16] and in 20% an antidepressant treatment preceded ALS [17].…”
Section: Introductionmentioning
confidence: 99%
“…The relation with the site of onset [14,18], gender [14,18,19], time since diagnosis [14,17,19,20] and physical impairment [14,15,18,21] is also controversial. Methodological problems, including small sample size and cross-sectional design, partly explain these inconsistencies.…”
Section: Introductionmentioning
confidence: 99%